PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN KONSUMEN MEMBELI PADA RUMAH MAKAN KHAS KAILI JALAN TEMBANG DI KOTA PALU - Pina, Pina (Fakultas Ekonomi Universitas Tadulako, 2016)
This research aims to know and analyze simultaneous and partial influence of service marketing mix (X), which consist of product (X1), price (X2), place (X3), promotion (X4), people (X5), physical evidence (X6), and process (X7) on consumer decision (Y) to buy at the Kailinese restaurant in Palu. Based on the result of multiple linear regressions, it is shown that service marketing mix consist of product, price, place, promotion, people, physical evidence, and process, simultaneously have significant influence on consumer decision to buy at the Kailiniese restaurant in Palu with the sig. value of 0,737 or 73,7 %. Partially, the study also shown that service marketing mix which consist of product, price, place, promotion, people, physical evidence, and process have significant influence on consumer decision to buy at the Kailinese restaurant in Palu with the sig. value of product = 0,559, price=0,085, place = 0,173, promotion = 0,042, people=0,201, physical evidence = 0,877, and process = 0,000. The most dominant variable that influences the decision of consumer is physical evidence.